Utilization of Milkfish Offal (Chanos chanos) as a Shrimp Paste Product with Different Salt Concentrations - Tri Widayati Putri; Annisa Wahdani; Jawiana Saokani Sofyan Sofyan (Indonesian Journal of Coastal and Marine Studies, 2025)
High milkfish production results in high processing waste, such as fish offal which is often simply disposed of without optimal utilization. This study aims to utilize milkfish offal as a raw material for making shrimp paste with variations in salt concentration. The study used the Complete Random Design (RAL) method with three different salt treatments, namely 0% as a control, 15% and 20%. The parameters tested included proximate analysis (water, carbohydrates, proteins, fats and ash) as well as sensory tests (appearance, aroma, taste and texture). The results of the proximate test showed 0% salt concentration with a water content value of 15.37%, carbohydrate content of 34.32%, protein content of 32.21%, fat content of 15.91%, ash content of 2.18%. Salt concentration is 15% with a water content value of 14.57%, carbohydrate content of 32.54%, protein content of 26.92%, fat content of 13.46%, ash content of 12.52%. Salt concentration 20% with a water content value of 14.71%, carbohydrate content 32.34%, protein content 24.52%, fat content 13.04%, ash content 15.39%. The results of the sensory test showed 0% salt concentration with a value of 7.8, smell 7.67, taste 7.13, texture 7.53. Salt concentration 15% with appearance value of 7.93, smell 8.33, taste 8, texture 7.4. Salt concentration 20% with appearance value 7.6, smell 7.73, taste 7.4, texture 7.07. In conclusion, the water, protein and sensory content have met the requirements of SNI (water max 35%, protein min 15% and sensory min 7), the results of ANOVA statistical analysis, show that the variation in salt concentration has a real effect on the proximate and has no real effect on the sensory value.